Characterization of protein-polyphenol interactions between novel plant proteins (pea and hemp) and blueberry polyphenols with respect to polyphenol binding and delivery - Chima, Bianca, author; Van Buiten, Charlene, advisor; Johnson, Sarah, committee member; Prenni, Jessica, committee member (Colorado State University. Libraries, 2022)
Despite the numerous health benefits associated with polyphenols, dietary intake of this class of compounds is low in the United States due to low intake of fruits and vegetables. It has been shown that dairy foods (i.e. milk, yogurt) increase polyphenol bioavailability due to polyphenols interacting with whey protein, enhancing polyphenol stability and uptake throughout digestion. However, increasing concerns for sustainability and health have introduced a variety of novel plant-based proteins as dairy alternatives. This study aimed to investigate the abilities of edible pea and hemp protein isolates to form complexes with blueberry polyphenol extract (BPE) and characterize the physical and biological functionalities of these complexes compared to whey proteins. Protein/polyphenol solutions were analyzed using UV-Vis spectroscopy to determine if complexation occurred. Secondary structures and binding affinities were analyzed by far-UV CD Spectroscopy and fluorimetry, respectively. In vitro digestion was performed to determine whether the protein profile changed in the presence of BPE via SDS-PAGE and determination of free amino acids using the ninhydrin method. Protein isolates from pea and hemp successfully formed complexes with BPE with binding affinities for the compound similar to whey protein. Relative helicity of the hemp protein was higher than the other protein sources and increased upon complexation with BPE. Furthermore, the SDS-PAGE profiles of all the proteins were the same whether BPE was present or not and the free amino acid content increased after digestion for the protein and protein/polyphenol solutions. Overall, complexation of BPE with plant proteins was successful. Fluorescence quenching and changes to the secondary structure of the proteins in the presence of BPE indicate that polyphenols were bound but the mechanisms and structures responsible for complexation seem to vary between proteins. More research is needed to determine the interactions that cause binding between the polyphenols and the proteins and whether the bioavailability of the compounds will increase when bound to the proteins in cell model and/or clinical study. This study provides a foundation for exploring the effects of plant-based proteins on phytochemical functionality in complex, "whole food" matrices.
Keywords: blueberries; pea protein; polyphenols; hemp protein; bioavailability; plant proteins